Avaliação da influência de tratamentos superficiais na absortância e morfologia de filmes absorvedores de Mo/SiO2 obtidos via Sputtering - Oliveira, Aline da Silva (2021)
Sustainable development is directly related to renewable energy sources. Among these sources is the Sun, from which practically all the energy used on the planet derives. Solar energy can be used to generate electricity through photovoltaic modules or thermal power plants that use electric generators, or used to heat water in solar collectors for direct use. The good thermal performance of solar collectors depends on the selective coverage that covers the absorber plate of the collectors, known as selective surfaces, which are materials with high capacity to absorb solar radiation and low infrared emission. Various materials and layer configurations can be used in manufacturing selective surfaces. This work proposes the production of selective surfaces in multilayers of molybdenum (Mo) and silica (SiO2) in order to optimize the thermal performance of the system, comparing different parameters in the sputtering deposition technique, and evaluating the influence of the type of substrate treatment on this performance. The results obtained in UV-Visible and Near Infrared Spectrophotometry showed that the surface absorptance is higher for Mo and Mo/SiO2 films on electropolished surfaces compared to treatments with acid and hexane. The highest absorptance reached was 98.10% for a Mo/SiO2 film. Band gaps were estimated by the Tauc method and assumed values ranging from 0.7 to 3.45 eV. These values increase with increasing film thickness, increasing absorptance. Higher band gap values indicate the formation of Cr2O3 in the film. In electropolished samples it was determined the existence of more than one energy gap that is related to the higher absorptance of these samples. Fourier Transform Infrared Spectroscopy (FTIR) indicated the presence of residues of materials used in the surface treatments of substrates and characteristic bands of the vibration of Cr2O3 bonds from chemical passivation, and a marked band characteristic of SiO2 bonds. X-ray diffraction (XRD) exhibited peaks characteristic of the metallic Mo phase, and the presence of silica in the amorphous and crystalline phases in the form of quartz was also verified. The results obtained in Optical Profilometry indicate that the absorptance of the samples is influenced by the roughness of the substrates. The thickness and roughness of the films were evaluated using Atomic Force Microscopy (AFM), which determined thickness values characteristic of thin films.